The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14202/ijoh.2016.75-80
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial residues in tissues and eggs of laying hens at Chittagong, Bangladesh

Abstract: Aim: Antimicrobial residue in animal food products is an important index of food safety. Antimicrobial residues could result from chemotherapeutic or chemoprophylactic use of drugs in food animals. This occurrence of residue in animal food products has received enormous worldwide attention from some local, international, and public health agencies. A crosssectional study was conducted from July to December 2009 to detect the antibiotic residues in tissues and eggs of laying hens at Chittagong of Bangladesh. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
4
11
0
1
Order By: Relevance
“…Indeed, this is an area of concern as numerous studies conducted in Bangladesh showed antibiotics in consumable meats, eggs, and fishes. 60 , 61 Respondents were divided into almost equal groups regarding their beliefs, whether physicians often prescribe antibiotics unnecessarily. Previous studies reported that physicians often prescribed two or more antibiotics, frequently with the higher generation; however, no study could depict that physicians prescribe antibiotics unnecessarily.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is an area of concern as numerous studies conducted in Bangladesh showed antibiotics in consumable meats, eggs, and fishes. 60 , 61 Respondents were divided into almost equal groups regarding their beliefs, whether physicians often prescribe antibiotics unnecessarily. Previous studies reported that physicians often prescribed two or more antibiotics, frequently with the higher generation; however, no study could depict that physicians prescribe antibiotics unnecessarily.…”
Section: Discussionmentioning
confidence: 99%
“…A high percentage of poultry meat and eggs meant for human consumption were found to have antimicrobial residues such as tetracycline, ciprofloxacin, enrofloxacin and amoxicillin [49,50]. The prevalence of antibiotic residues varied from >60% in liver, kidney, and eggs to around 50% in breast and thigh samples [49]. In Bangladesh, 3,079 metric tons of poultry manure is produced per day and 50% of this is directly used in aquaculture [51].…”
Section: Situation In Food Animals Fisheries and Environment Includmentioning
confidence: 99%
“…Ampicillin and Amoxicillin antibiotics resistant might have been due to use as growth promoters. Cross antimicrobial resistance cannot be ignored as it is evident in many earlier studies and causes higher resistance to Ampicillin and Amoxicillin [15,30,31].…”
Section: R (%) I (%) S(%) N R (%) I (%) S (%) N R (%) I (%) S (%)mentioning
confidence: 99%
“…Worldwide Salmonella is a significant food and water-borne zoonotic pathogens [14]. In developing countries like Bangladesh antimicrobial resistance occur due to an increased and indiscriminate use of antibiotics in food animals, environments and human [6,15]. Throughout the previous era, multi-drug resistance of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%